The shorter Routledge encyclopedia of philosophy - Craig, Edward (Routledge, 2005)
The Shorter REP presents the very best of the acclaimed ten volume Routledge Encyclopedia of Philosophy in a single volume. It makes a selection of the most important entries available for the first time and covers all you need to know about philosophy, from Aristotle to Wittgenstein and animals and ethics to scientific method. Comprising over 900 entries and covering the major philosophers and philosophical topics, The Shorter REP includes the following special features: